Situation analysis of cataract surgery in poverty-stricken region of Yixing in Jiangsu - Huan Yang (Guoji Yanke Zazhi, 2014)
AIM: To explore the feasibility and evaluation on prevention of blindness in poverty-stricken region of Yixing led by the People's Hospital. METHODS: By respectively comparing poverty-relief(hereafter referred to as poverty)patients in poverty-stricken region with the patients in urban district(hereafter referred to as urban)in the following aspects: the situation of visual blindness and the visual disability before surgery and the situation of vision rehabilitation and getting rid of visual disability after operation, and then the differences were analyzed as the standard: blindness was vision less than 0.05, visual disablity was vision less than 0.3 and vision rehabilitation was postoperative vision equal to or more than 0.05 and getting rid of visual disability was postoperative vision equal to or more than 0.3. The differences were compared between the cataract surgery situation in poverty-stricken region led by our hospital and the requirements of “The prevention of blindness project for millions of poor cataract patients” during the twelfth five-year. RESULTS: There were 72 cases in the poverty group, including 41 cases of blindness and 70 cases of visual disability, while totally 210 cases were in the urban group, including 111 cases of visual blindness and 200 cases of visual disability. There were no difference between the poverty group and urban group in the visual blindness(χ2=1.344, P<0.05)and in the visual disability(χ2=0.146, P<0.05)preoperatively. The rate of vision rehabilitation was 92.7% in poverty group and 88.3% in urban group(χ2=0.236, P<0.05)and there were no difference for vision rehabilitation between the two groups. The rate of vision equal to or more than 0.3 after operation was 78.6% in poverty group and 73% in urban group(χ2=0.846, P<0.05)and there were no difference for vision equal to or more than 0.3 after operation between the two groups. CONCLUSION: “The prevention of blindness project for millions of poor cataract patients” has been carried out smoothly in our hospital which proves that we do have the ability to undertake the prevention of blindness in our city, but there is still some deficiency to be improved.